OCCUPATIONAL HEALTH SERVICE & EDUCATION FOR TAPIS CRAFTMAN IN NEGERI KATON VILLAGE - Saftarina, Fitria; Isti Angraini, Dian; Indria Anggraini, Dwi; Karimah, Nisa (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
Informal sector workers are workers who are most vulnerable to various risks that cause health problems. Health and safety issues related to their work can interfere with their productivity. Tapis craftsmen in the Negeri Katon Village,Pesawaran Regency, Lampung is part of the Tapis Jejama UMKM. Based on interviews with the UMKM coordinator, it was found that the craftsmen complained of back, neck, arm, and hand pain and symptoms of anemia. This interferes with the productivity of Tapis craftsmen. This service aims to improve the occupational health status of filter craftsmen in Negeri Katon Village to support work productivity in both health and economic aspects. The benefits of this activity are to reduce the incidence of anemia, musculoskeletal pain and help strengthen Negeri Katon Village as a Creative Tourism Village. The activity was carried out with a target of 30 tapis craftsmen. The solutions offered are occupational health services for tapis craftsmen, health education about ergonomics, occupational nutrition, and the stretching benefits. The results obtained that 100% of workers complained of musculoskeletal pain, as many as 5 people (8.3%) got hypertension and as many as 12 people (40%) got anemia. Before education, the knowledge of filter craftsmen about health risks in their work was 68% and after education is carried out, there is an increase of 97%. This activity needs to be carried out with the establishment of the Pos Upaya Kesehatan Kerja (UKK) as an effort to maintain the health of tapis craftsmen in Negeri Katon Village, Pesawaran Regency, Lampung.